Relationship the Work Environment and Leadership with ASN Performance Employee at Secretariat DPRD Office South Bengkulu - Afridi Midian; Neri Susanti; Kaulan Kaulan (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
This research aim to know relationship of the work environment and leadership with ASN performance employee at Secretariat DPRD Office South Bengkulu. Method data collecting with propagated kuesioner to 52 employee poepel at Secretariat DPRD Office South Bengkulu. Analysis Data conducted with spearman rank corelation and hypothesis testing with t-test. The result showed spearman rank corelation (ρ) of the work environment with performance employee equal to 0,637, strong criterion; The relationship of organizational culture with performance employee was 0,557, moderate criterion. There is a significant relationship between the work environment with ASN performance employee at Secretariat DPRD Office South Bengkulu, are known that tcount is greater than ρtabel, 5,844 > 1,676, Ho is rejected and Ha is accepted. There is a significant relationship between leadership with ASN performance employee at Secretariat DPRD Office South Bengkulu, are known that tcount is greater than ttabel, 4,742 > 1,676, Ho is rejected and Ha is accepted.